Currency hedging for international stock portfolios: The usefulness of mean–variance analysis - de Roon, Frans A.; Nijman, Theo E.; Werker, Bas J.M. (Journal of Banking & Finance, 2003)
We test whether hedging currency risk improves the performance of international stock portfolios.We show that an auxiliary regression provides a wealth of information about the optimal portfolio holdings for non-mean–variance investors, analogous to the information provided by the Jensen regression about optimal portfolio holdings for the mean–variance case. We find that static hedging with currency forwards does not lead to significant improvements in portfolio performance for a US-Dollar based stock portfolio from the G5 countries, whereas dynamic hedges that are conditional on the interest rate spread do. These conclusions hold for both mean–variance and power utility investors and show up both in-sample and out-of-sample. However, the optimal forward positions can differ significantly for both types of investors.